Evaluation of Side Effects of Corticosteroid Eye Drops in Post-Cataract Surgery Patients - Sholihah, Riyadatus; Haris, M. Shofwan (Universitas Pahlawan Tuanku Tambusai, 2025)
Corticosteroids are natural steroid hormones in humans produced by the adrenal cortex gland that have a function to treat inflammation or autoimmune disorders in the body. In the case of eye disease, corticosteroid drugs can take the form of eye drops that are widely used in post-cataract surgery patients, which function to reduce inflammation that occurs in the interior segment which sometimes has no apparent cause. The purpose of this study was to determine the side effects that can occur in the use of corticosteroid drugs after cataract surgery. This study was conducted with a crossectional method, which was analysed descriptively using the universal sampling method. This activity uses inclusion and exclusion criteria. The sampling method uses non-random sampling with the time limited sampling method, namely taking all patient's Health Medical Record data. The results and discussion of this study were conducted at the KMU Madura Clinic Pharmacy Installation involving a number of post-cataract surgery patients who used corticosteroid eye drops. The use of corticosteroid eye drops has the potential to cause various side effects. The most common side effects encountered in patients are blurring, stinging, red eyes, and itching. The most widely used eye drops were prednisolone by 53.3%. Based on the above results, it can be described that the length of use of corticosteroid eye drops in patients after cataract surgery at the KMU Madura Eye Clinic pharmacy installation is more than 30 days.